2021
DOI: 10.1029/2020jd034325
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Aerosol Indirect Effects on Cloud Streets Over the Northwestern Pacific Ocean

Abstract: We simulated aerosol effects on cloud streets formed during continental cold‐air outbreaks over the Northwestern Pacific using an aerosol‐sensitive cloud microphysical scheme coupled with the Weather Research and Forecast model. The micro‐ and macro‐scale responses were examined under a wide range of aerosol concentrations. The cloud streets generally remain in a transient state, indicating that the aerosol particles may significantly affect the cloud system's development. The simulation results revealed a cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 103 publications
(266 reference statements)
0
3
0
Order By: Relevance
“…While increased mixing with the free atmosphere may lead to cloud deepening, when the boundary layer unstable, it may also lead to an early onset of cloud breakup processes through evaporation-entrainment (Small et al, 2009). In some cases, increased entrainment and evaporation at the cloud top could lead to reduced cloud top heights, which is the opposite of an invigoration effect (Xue and Feingold, 2006). Whether the growth of a particular cloud is enhanced or inhibited may depend on the distribution of liquid water near the cloud top and the ability of the cloud to penetrate the free atmosphere.…”
Section: Aerosol Effects On Evaporative Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…While increased mixing with the free atmosphere may lead to cloud deepening, when the boundary layer unstable, it may also lead to an early onset of cloud breakup processes through evaporation-entrainment (Small et al, 2009). In some cases, increased entrainment and evaporation at the cloud top could lead to reduced cloud top heights, which is the opposite of an invigoration effect (Xue and Feingold, 2006). Whether the growth of a particular cloud is enhanced or inhibited may depend on the distribution of liquid water near the cloud top and the ability of the cloud to penetrate the free atmosphere.…”
Section: Aerosol Effects On Evaporative Processesmentioning
confidence: 99%
“…Below-cloud evaporation and its associated cooling destabilizes the boundary layer, which could then further invigorate the cloud layer through amplified turbulence (Xue and Feingold, 2006). The effects of below-cloud evaporation on the stability are sensitive to the location of the cooling and drop size of the cloud; it is possible in some circumstances that cooling can act to stabilize the boundary layer.…”
Section: Aerosol Effects On Evaporative Processesmentioning
confidence: 99%
“…Previous investigations of precipitation processes in marine stratocumulus have been mainly focused on the formation of drizzle and light rain associated with the changes in cloud microphysics and dynamics, predominantly for the persisting low cloud decks over the northeastern and southeastern Pacific (Wood, 2012). Over the northwestern Pacific, where the East Asian winter monsoon is active, transient marine stratocumulus clouds are formed in the regions where the near-surface northeasterly monsoonal wind is enhanced by the synoptic systems (Koike et al, 2012;Koike et al, 2016;Liu et al, 2016;Wu and Chen, 2021), as shown in the example in Figure 1a. With the presence of the marine stratocumulus, the boundary layer is moistened through enhanced vertical mixing (Lilly, 1968).…”
Section: Introductionmentioning
confidence: 99%